Pedagogies of Disruption and the Challenge of Social Justice under Regimes of Neoliberalism - Henry A. Giroux (Universidad Autónoma de Madrid, 2015)
Nowadays we find ourselves in a socio-political situation called neoliberalism, the last stage of capitalism, the most ruthless, and is characterized by a latent economic, social and democratic crisis. Modern societies are living in a constant war where racism, globalization and social injustice are the undisputed protagonists of today. Faced with this situation, education has the power to fight against this reality. It is important to be aware of the fundamental political role of education, considering that shapes the way in which future citizens think, wish and act. Education has in his hands the power of create intellectuals who fight against oppression and to be agents of social change. Higher education is therefore one of the few public spheres that has the ability to have a real democratic culture and thus change the course of history.